Case Report: Unmanipulated Matched Sibling Donor Hematopoietic Cell Transplantation In TBX1 Congenital Athymia: A Lifesaving Therapeutic Approach When Facing a Systemic Viral Infection - Chitty-Lopez, Maria; Duff, Carla; Vaughn, Gretchen; Trotter, Jessica; Monforte, Hector; Lindsay, David; Haddad, Elie; Keller, Michael D.; Oshrine, Benjamin R.; Leiding, Jennifer W. (Frontiers in Immunology, 2022)
Congenital athymia can present with severe T cell lymphopenia (TCL) in the newborn period. TCL can be detected by decreased T cell receptor excision circles (TRECs) through newborn screening (NBS). The etiology of TCL may be associated with hematopoietic or primary thymic defects, and genetic testing is pivotal in establishing a definitive diagnosis. The most common thymic stromal defect causing selective T cell lymphopenia is 22q11.2 deletion syndrome (22q11.2DS). T-box transcription factor 1 (TBX1), present on chromosome 22, is responsible for thymic epithelial development and has been described as a significant genetic determinant in 22q11.2 deletion syndrome. Single variants in TBX1 causing haploinsufficiency cause a clinical syndrome that mimics 22q11.2DS. Definitive therapy for congenital athymia is allogeneic thymic transplantation. However, availability of such therapy is limited. Furthermore, congenital athymia can be complicated by developing Omenn syndrome (OS) in the context of infection. We present a patient with early diagnosis of congenital athymia due to TBX1 haploinsufficiency. While evaluating for thymic transplantation, she developed OS and life-threatening adenoviremia. The patient partially responded to virus-specific T cell infusions but ultimately required unmanipulated matched sibling donor (MSD) hematopoietic cell transplant to achieve post-thymic donor-derived engraftment, viral clearance, and lasting immune reconstitution. This case illustrates that upon restricted availability of thymus transplantation, clinicians may consider cytotoxic T cell therapy and hematopoietic cell transplantation to treat congenital athymia patients with severe infections.